2021
DOI: 10.3390/v13040619
|View full text |Cite
|
Sign up to set email alerts
|

Differential Influence of Age on the Relationship between Genetic Mismatch and A(H1N1)pdm09 Vaccine Effectiveness

Abstract: Assessment of influenza vaccine effectiveness (VE) and identification of relevant influencing factors are the current priorities for optimizing vaccines to reduce the impacts of influenza. To date, how the difference between epidemic strains and vaccine strains at genetic scale affects age-specific vaccine performance remains ambiguous. This study investigated the association between genetic mismatch on hemagglutinin and neuraminidase genes and A(H1N1)pdm09 VE in different age groups with a novel computational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…The HA and NA protein sequences in the United States were collected for model building and genetic data in the United Kingdom, Germany and Hong Kong were collected for validation. The vaccine effectiveness data were extracted from published epidemiological studies and described in the supplementary materials of Cao et al 2021 5,6 . The influenza vaccine strains recommended by WHO for use in the northern hemisphere were summarized in supplement materials Table S1 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The HA and NA protein sequences in the United States were collected for model building and genetic data in the United Kingdom, Germany and Hong Kong were collected for validation. The vaccine effectiveness data were extracted from published epidemiological studies and described in the supplementary materials of Cao et al 2021 5,6 . The influenza vaccine strains recommended by WHO for use in the northern hemisphere were summarized in supplement materials Table S1 .…”
Section: Methodsmentioning
confidence: 99%
“…Previously, we developed a novel computational framework to predict VE for the influenza 5,6 and COVID-19 7 vaccine by virus sequencing data. We found that genetic distance (GD) between vaccine strains and circulating viruses is significantly correlated with vaccine effectiveness (VE).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we drew the connection between genetic mismatch of circulating SARS-CoV-2 viruses and reported COVID-19 VE from population studies. Based on previous bioinformatics approach established for the influenza viruses 16,17 , we further advanced the VE estimation framework for COVID-19 by controlling the clustered random variation of technology platforms using a mixed-effects model. Through extensive analysis of worldwide VE studies and genetic sequences, we showed that a significant proportion of the change in VE could be explained by the genetic factor and provided an efficient framework to evaluate vaccine protection.…”
Section: Mainmentioning
confidence: 99%